2010
DOI: 10.1111/j.1365-3040.2010.02129.x
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal responses to humidity and temperature in darkness

Abstract: Stomatal responses to leaf temperature (Tl) and to the mole fractions of water vapour in the ambient air (wa) and the leaf intercellular air spaces (wi) were determined in darkness to remove the potential effects of changes in photosynthesis and intercellular CO2 concentration. Both the steadystate and kinetic responses of stomatal conductance (gs) to wa in darkness were found to be indistinguishable from those in the light. gs showed a steep response to the difference (Dw) between wa and wi when wa was varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 28 publications
(47 reference statements)
3
79
1
1
Order By: Relevance
“…and water transport. Recent studies support the idea that water in the guard cell wall is normally maintained by, and equilibrates with, the vapor phase within the intercellular air space of the leaf (Shope et al, 2008;Mott and Peak, 2010;Pieruschka et al, 2010;Rockwell et al, 2014). Since gaseous exchange within the leaf is extremely rapid (Sack and Holbrook, 2006;Morison et al, 2007;Peak and Mott, 2011), this equilibrium implies that the water potential of the guard cell wall is coupled directly to the surrounding air space within the substomatal cavity and it suggests a formal basis for connecting the macroscopic conductance of the leaf with the microscopic processes of the guard cell.…”
Section: Discussionmentioning
confidence: 80%
“…and water transport. Recent studies support the idea that water in the guard cell wall is normally maintained by, and equilibrates with, the vapor phase within the intercellular air space of the leaf (Shope et al, 2008;Mott and Peak, 2010;Pieruschka et al, 2010;Rockwell et al, 2014). Since gaseous exchange within the leaf is extremely rapid (Sack and Holbrook, 2006;Morison et al, 2007;Peak and Mott, 2011), this equilibrium implies that the water potential of the guard cell wall is coupled directly to the surrounding air space within the substomatal cavity and it suggests a formal basis for connecting the macroscopic conductance of the leaf with the microscopic processes of the guard cell.…”
Section: Discussionmentioning
confidence: 80%
“…2A, top right panel). Under high-humidity conditions, stomates will remain open in the dark (Barbour and Buckley, 2007;Mott and Peak, 2010), and again, guard cells showed high GUS staining ( Fig. 2A, bottom right panel).…”
Section: Apy1 and Apy2 Promoter Activities And Protein Levels Correlamentioning
confidence: 95%
“…1C) raises questions about the origin of this nocturnal water loss. Although recent studies have shown that stomata remain partially open in the dark (30,31), including in grapevine (32), a slightly permeable cuticle might also be responsible for these observations. To decipher the respective contributions of stomata and cuticle to the genetic variability of E n , a subset of 28 genotypes with contrasting E n were selected from the S×G population.…”
Section: Genetic Variability In Nighttime Transpiration Mostly Originmentioning
confidence: 98%